MODAL EKONOMI DAN MODAL SOSIAL TRADISI TURUN MANDI BAYI DI DESA PULAUMUNGKUR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Meci Indrayani; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The tradition of bathing a baby in Pulau Mungkur Village, Gunung Toar District, Kuantan Singingi Regency is a celebration of the birth of a child and an expression of gratitude to Allah SWT, who previously mothers and babies were not allowed to leave the house, by doing this tradition they can leave the house freely.The formulation of the problem discussed in this study is economic capital in the tradition of Baby Bathing in Pulau Mungkur Village, Gunung Toar District, Kuantan Singingi Regency. The informants from this study amounted to 7 people where these informants consisted of traditional stakeholders, the leaders of the Baby Bathing Drops, and the community who had carried out the Baby Bathing Drops tradition. Research uses the type of qualitative descriptive research. The technique in the study was selected using a purposive sampling technique. The theory used is the theory of economic capital and social capital put forward by Putnam which consists of networks, norms, beliefs. The results of the study that economic capital and social capital are very important in the implementation of the Baby Bathing Baby Tradition in the Mungkur Island community. Economic capital and social capital are very important, namely with the existence of economic capital and social capital in carrying out Baby Bathing in Pulau Mungkur Village it can be carried out because in the Baby Bathing Descend tradition requires economic capital, namely to buy the requirements for Baby Bathing, and social capital is also very important in tradition of Baby Bathing. Keywords: Tradition, Turun Mandi Bayi, Society